Desenvolvimento de argamassa colante polimerizada para aplicação de revestimentos cerâmicos em fachadas - Stefane Jardim Vitorino (2019)
Fourteen variations of adhesive mortars were measured by varying the polymer type and combining them with cement in two different proportions, water retainer and additions, which provided the mortars with adequate consistency for application on facades. The objective was to evaluate the performance of adhesive mortars based on the characteristics of the polymers and the percentage of cement applied, in order to verify their flexibility for use in facades exposed to climatic variations and much requested by structural deformations. The tests of the samples were limited to the Brazilian technical norms, but from the choice of 4 variations, the analysis of the open time and its adhesion extension were important for the deepening of the study that consisted in the development of a mortar for use in facades. The results of the four variations were satisfactory in their adhesion forces for the classification of these samples as ACII according to the Brazilian normative criteria. From the results obtained in the deformability tests, it was found that, regardless of the types of polymers added to the compositions, adhesive mortars can demonstrate greater deformability by adding a polymer with its glass transition temperature closer to the ambient temperature measured during the test, Balancing with the cement dosage for better performance of the adhesive mortar in its interface with the ceramic, in order to verify, after studies, the durability requirements due to its deformability.